Solving Innovative Problems of Thrust Vector Control Based on Euler's Scientific Legacy - Yuri A. Sazonov; Mikhail A. Mokhov; Inna V. Gryaznova; Victoria V. Voronova; Khoren A. Tumanyan; Egor I. Konyushkov (Salehan Institute of Higher Education, 2023)
This study aims to develop an interdisciplinary approach to solving innovative thrust vector control problems. The methodology involves the development of a working hypothesis about the ejection process when using a controlled nozzle to deflect the thrust vector (velocity vector) in any direction within a complete geometric sphere. When developing the working hypothesis, a multilateral analysis of individual facts and scientific and technical information is performed using tools in the